HASIL BELAJAR KOGNITIF FISIKA SISWA MELALUI PENERAPAN STRATEGI METAKOGNITIF PADA SISWA KELAS XII MIA 1 SMAN 8 PEKANBARU - Lindah Permata Sari; Zuhdi Ma’aruf; Azizahwati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study is to describe the cognitive learning outcomes of student’s physics through the application of metacognitive strategies. The research method used is Pre-Experimental by using One Shot Case Study design. This research was conducted at SMAN 8 Pekanbaru in May 2016 until June 2017 with research subject at Class XII MIA 1 consisting of 35 students. The data in this study is the results of student's cognitive learning outcomes test which are diagnostic test in the form of multiple choice reasoned amounted to 10 questions. The data analysis used is descriptive analysis that is by determining the absorption and learning difficulties of student. Based on data analysis, the result shows that the average absorption of students Class XII MIA 1 is 70,7% which is in good category. For the analysis of the student's learning difficulties, the result is that at each stage of problem solving on metacognitive strategy shows that from 34 students almost half of them have difficulty in understanding stage of problem, problem solving planning stage and interpretation stage, and only a small part having difficulties in planning stage plan. This means that students have the ability to process data in a good mathematical form.Key Words: Cognitive learning outcomes, Metacognitive strategies, Electrostatic concept